PENGGUNAAN MEDIA PEMBELAJARAN DIORAMA UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V-F DI SDN TANAH KALIKEDINDING V SURABAYA - Sherli Pentianasari; Ade Firmannandya (Universitas Muhammadiyah Surabaya, 2022)
This study aims to describe student activities, teacher activities and learning outcomes. The type of research used is classroom action research which consists of 2 cycles. Each cycle includes the stages of planning, action, observation, and reflection. The subjects of this study were students of class V-F SDN Tanah Kalikewall V Surabaya which consisted of 38 students with details of 19 students and 19 students. The instrument used to reveal the activity data of students and teachers used an observation sheet. Meanwhile, to reveal the data on learning outcomes, a test instrument was used. The results showed that the student activity data in the first cycle reached 70% while the second cycle reached 95% which had increased by 25%. The teacher activity data in the first cycle reached 70% while in the second cycle it reached 95% which had increased by 25%. Data on student learning outcomes in the first cycle was 73.63% while in the second cycle it reached 88.47% which had experienced an increase of 15.47%. These data indicate that the use of diorama media can increase student activity, teacher activity and student learning outcomes in class V-F SDN Tanah Kalikewall V Surabaya.Â Keywords: diorama media, student activities, teacher activities, and learning outcomes